Numerical analysis of cellular steel beams failure modes in fire conditions - Jaqueline, A.S. (2020)
Cellular beam generally originates from steel hot-rolled I-section member, which the web is cut, displaced and subsequently welded (Westok method) to obtain openings in the web spaced regularly, with different forms like circular, sinusoidal or hexagonal, see Figure 1. The procedure results in a deeper beam, approximately 40-60% deeper than its parent solid section, [1]. This type of beam is increasingly used because it is capable to support long spans, it can have a bending resistance up to 2.5 times higher than its parent section and its openings allow the passage of technical equipment and ventilation systems through their web, which reduces the floor height and therefore the overall height of building. The presence of the opening influences in the failure modes of the beam. Vierendeel mechanism and web post buckling (WPB) are examples of failure modes originate due the openings, while already existing failure modes on solid beams are modified in cellular beams, such as lateral-torsional buckling (LTB), [2]. Besides that, exposure to high temperatures has a detrimental effect on the steel resistance, which added to the initial imperfections of the beam results in the combination of failure modes previously mentioned. For that reason, the main purpose of the study will be to define the failure modes, in particular WPB and LTB, and the beam resistance, relating the temperature with variant geometric parameters, comparing the results obtained by simple calculation methods proposed by Eurocode 3 and Steel Construction Institute (SCI) with numerical results. For this purpose, a finite element model is developed in the software Ansys to study the influence of different geometric parameters, considering geometric imperfections and residual stresses in the beams. Results are compared considering different geometric characteristics and temperatures with design values obtained from the Eurocode EC3-1-2 and the Eurocode new draft EC3-1-13, [3].